2018
DOI: 10.1002/aps3.1020
|View full text |Cite
|
Sign up to set email alerts
|

Pollen sleuthing for terrestrial plant surveys: Locating plant populations by exploiting pollen movement

Abstract: Premise of the StudyWe present an innovative technique for sampling, identifying, and locating plant populations that release pollen, without extensive ground surveys. This method (1) samples pollen at random locations within the target species’ habitat, (2) detects species’ presence using morphological pollen analysis, and (3) uses kriging to predict likely locations of populations to focus future search efforts.MethodsTo demonstrate, we applied the pollen sleuthing system to search for artificially construct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 77 publications
(85 reference statements)
1
5
0
Order By: Relevance
“…Solitary insects and pollinators without floral constancy could also be investigated for their potential in detecting boneseed. A study using artificial pollen has shown that trapping of solitary insects could be used as a method to detect populations of invasive plants, and that these can be detected at low density although with decreased ability to track the detection to a source population (Campbell et al, 2018). Other studies have identified pollen on insects collected in traps, although not from low‐density plant populations (Gill & O'Neal, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Solitary insects and pollinators without floral constancy could also be investigated for their potential in detecting boneseed. A study using artificial pollen has shown that trapping of solitary insects could be used as a method to detect populations of invasive plants, and that these can be detected at low density although with decreased ability to track the detection to a source population (Campbell et al, 2018). Other studies have identified pollen on insects collected in traps, although not from low‐density plant populations (Gill & O'Neal, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although these identifications often require specialist expertise and may achieve low taxonomic resolution due to the lack of morphological characters for species-level identification (Bell et al, 2016;Khansari et al, 2012;Rahl, 2008). Moreover, even when plant taxa are detected from pan traps, they are rarely used to infer species-specific flower visits or pollen transport (Popic et al, 2013); the primary reasons being that (1) pollen collected from pan traps represents foraging from the entire community of arthropods captured, and; (2) pan trap plant detections may include nontarget wind-pollinated species, which could result from contamination, either airborne pollen/plant material (Johnson et al, 2019b) or herbivorous regurgitant (Sword, 2001), rather than flower visits (Campbell et al, 2018;Popic et al, 2013). Such contributions may be significant considering that wind-pollinated species produce copious quantities of pollen (see Harrington & Metzger, 1963).…”
Section: Introductionmentioning
confidence: 99%
“…Such contributions may be significant considering that wind-pollinated species produce copious quantities of pollen (see Harrington & Metzger, 1963). Despite this potential for contamination, ambient pollen (pollen dispersed by air, not invertebrates) is rarely quantified, with studies instead relying upon alternative approaches, such as artificial pollen (see Campbell et al, 2018), to circumvent this issue. Plant surveys using passive traps may, therefore, benefit from alternative approaches, like those afforded by environmental DNA (eDNA) metabarcoding, to detect both pan trap-specific and ambient pollen, in order to generate high-throughput and high-resolution pollen datasets, which can help form robust conclusions about the plant resources used by pollinator communities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations